Model of Urban Information and Educational Space of Pedagogical Interaction - Mikhail A. Rodionov; Irina V. Akimova; Margarita A. Gavrilova; Zhanna Dedovets (Communications of International Proceedings, 2020)
This article considers the pertinent issue of building a model of a person-oriented urban educational environment for teachers. As a prerequisite for building this environment for teachers, the authors consider a University Educational Complex organized in 1990, which in various years included such divisions as a multidisciplinary college, a pedagogical lyceum for rural schoolchildren,  the  V.G. Belinsky Pedagogical University school of early development, a kindergarten, a teacher training college, and a graduate school The authors describe the basic principles of forming an urban person-oriented educational environment, as well as the main opportunities that this environment opens up. The result of building this environment is a significant increase in the professional competence level of teachers.
Keywords: Model; Person-Oriented Urban Educational Environment; Competence; Teacher